From inclusion to empowerment: advancing equity through co-research with people living with dementia - Hung, Lillian; Wong, Joey; Wong, Karen Lok Yi; Ong, Emily; Johnson, Granville; Rochford-Brennan, Helen; Mann, Jim; Gierach, Lester; Jackson, Lynn; Gregorio, Mario; Wighton, Mary Beth; Fehr, Phyllis (Frontiers in Dementia, 2025)
Too often, people living with dementia are spoken for rather than spoken with. This reflects deeply embedded assumptions/biases about people living with dementia in our society. This article explores the experiences and insights of individuals with dementia, positioning empowerment as a foundational strategy to advance social citizenship and equity. We collaboratively on more than a decade of shared work in research and advocacy. Our collective analysis identifies three key dimensions essential for meaningful empowerment: (a) recognizing strengths and building capacities, (b) equitable leadership, and (c) supportive environments and learning together. Our findings demonstrate that intentional, respectful collaboration produces extensive social, political, and healthcare benefits, actively challenging inequities and fostering a deeper sense of belonging and contribution.